LITERATA: Equitable Access for Students with Disabilities Through Inclusive Curriculum Developments - Puteh, Cut Fazila Safira; Budiman, Meghan Amelia; Setiawan, Adsila Luna Putri (Politeknik Assalaam Surakarta, 2026)
Education is a key tool for personal and societal growth, providing the knowledge and skills needed to thrive in a complex world. This study explores the development and implementation of LITERATA, an inclusive and disabilities-friendly curriculum designed to improve access to quality education for students with disabilities in Binjai, North Sumatra. Using a qualitative approach, the research draws on secondary data from academic publications, government policies, and case studies of inclusive programs. A comparative analysis method was applied to evaluate gaps between national regulations and actual school practices, while thematic coding helped uncover recurring challenges. The results show that many students still face significant barriers, ranging from a lack of trained teachers to insufficient learning resources. LITERATA responds by offering adaptive teaching methods, accessible materials like braille and digital platforms, and the integration of life and soft skills. The curriculum is supported by a structured three-year implementation plan involving stakeholders from local governments, educators, and community groups. Overall, the study finds that LITERATA offers a promising and scalable model for inclusive education that prioritizes equity, accessibility, and long-term sustainability.